The Effects of Immunoregulatory Therapies on Human Macrophage Function and Metabolism: Implications for Mycobacterial Infections and Diseases - Thong, Lorraine Wan (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2025)
Tuberculosis (TB), an endemic infecƟous disease caused by Mycobacterium tuberculosis (Mtb) is a huge burden globally. Dexamethasone is a potent long-acƟng syntheƟc glucocorƟcoid (GC) and presently, the role of GC as an adjuncƟve treatment for TB is limited and debatable. The aim of this study was to examine the effect of dexamethasone on human macrophage responses during Mtb infecƟon. The in vitro study in this thesis demonstrates that dexamethasone reduces glycolysis, cytokine producƟon, and caspase 3/7 related cell death in human macrophages sƟmulated or infected with Mtb. Consequently, there is an increased ability of the macrophage to kill Mtb in an autophagy associated process. This highlights the potenƟal that GC might possess as an adjuncƟve therapy for Mtb infecƟon and TB disease. Mycobacterium avium complex (MAC) is the most common cause of non-tuberculous mycobacterium (NTM) infecƟons. Thus far, no adjuncƟve therapies have been developed to work alongside anƟ-microbial therapy. The aim was to elucidate the immunometabolic profile of human macrophages infected with MAC and if dexamethasone could alter macrophage responses. The data is this study demonstrates that while dexamethasone reduces glycolysis and inflammatory mediators in human macrophages, it did not influence the clearance of M. avium bacilli by macrophages. This study highlights that inhibiƟon of inflammatory responses with GC alongside exisƟng anƟ-microbial therapy may be a strategy in treaƟng NTM infecƟon by limiƟng deleterious inflammaƟon. AnƟ-TNF-α therapies have been known to increase suscepƟbility to Mtb infecƟon and lead to acƟve TB disease, however, certain anƟ-TNF-α therapies have a higher risk factor for this compared to others. Therefore, the effects of different anƟ-TNF-α therapies on the metabolic and immunological profile of human macrophages was examined. Data in this study demonstrates that human monoclonal IgG, adalimumab, and infliximab reduce glycolysis in human MDM sƟmulated with Mtb, while etanercept did not. This reducƟon in glycolysis can be prevented by blocking Fc gamma receptors (FcϒR) indicaƟng immunometabolism in human macrophages can be regulated by FcϒR. This data will help with the development of future therapies targeƟng TNF-α by limiƟng off target effects that can downregulate the host immune system.
APPROVED